The Influence of Brand Image, Service Quality, Price Perception and Trust on the Purchase Decision of Welding Workshop Welding Www.Kanopirumah.Com - Juhaeri Juhaeri (Universitas Negeri Makassar, 2020)
Www.kanopirumah.com is a business that is engaged in the welding workshop business. To determine the effect of brand image on purchasing decisions, service quality on purchasing decisions, price perceptions of purchasing decisions, trust in purchasing decisions, and to know together with the influence of a brand image, service quality, price perceptions and trust in purchase decisions for welding shop services www.kanopirumah.com. This research is quantitative research. The population in this study are consumers who conduct transactions at the welding workshop www.Kanopirumah.Com. in this study as many as 100 consumers. Data collection methods in this research are observation, documentation study, and literature study. The method of data analysis is a simple linear regression test, product-moment correlation test, determination test, and hypothesis test (t-test). Data processing using Statistical Social Science Program (SPSS) version 22.00. The results showed that (1) Brand image influenced purchasing decisions with a t-test value of 2.329, sig. 0.022 <α = 0.05, thus proving the hypothesis that the brand image influences the purchase decision. (2) Quality of service influences purchasing decisions with a t-test value of 2.277, sig. 0.025 <α = 0.05, thus proving the hypothesis that service quality affects the purchasing decision. (3) Price perception influences purchasing decisions with a t-test value of 3.093, sig. 0.003 <α = 0.05, thus proving the hypothesis that price perception influences the purchase decision. (4) trust influences purchasing decisions with a t-test value of 3.215, sig. 0.002 <α = 0.05, thus proving the hypothesis that states' trust has an effect on purchasing decisions. (5) Brand image, service quality, price perception, and trust affect purchasing decisions.